SAMPLING AND REGIME PARAMETERS COMPUTATIONS OF PERCUSSIVE CONDENSER WELDING WITH MAGNETIC PULSED DRIVE - Stanislav V. NESKOROMNIY; Evgeny L. STRIZHAKOV (Advanced Engineering Research, 2010)
The scientifically based algorithm of process and equipment of hairpins with thin-walled details characterization is considered. The results of the chosen and calculated parameters of process and equipment are presented.